Ecological Interpretation of Regional Elements in the Design of Local and Korean Urban Public Facilities - Zhang, Yueting (Journal of Theory and Practice of Social Science, 2023)
In the planning and construction of modern city, how to highlight the regional elements of the city and show the ecological design of the city has become the key content. Public facility design is an important part of urban construction. On the one hand, it is directly related to the public life, and on the other hand, it is closely related to the urban context and future development. Based on this, this paper mainly discusses the regional elements and ecological interpretation in the design of urban public facilities in our country and South Korea, aiming to provide reference for the subsequent design. To answer our research question, we begin by constructing a sample of all Chinese non- financial firms listed in the A-share market between 2007 and 2018 (n=29,181). We obtain financial statement data from the China Stock Market and Accounting Research (CSMAR) database. We obtain individual audit partner’s demographic information, such as gender and educational background, from the Chinese Research Data Services CARD database and the China Institute of Certified Public Accountants (CICPA) website. We lose 1,674 observations because we cannot find the signing auditor’s demographic information needed in the Heckman’s model and PSM; we further delete 4,783 observations because they do not have enough firm financial data to compute the variables used in our empirical tests; we exclude 672 observations because the annual reports are signed with three auditor signatures. Our final sample consists of 22,052 firm-year observations.